2016
DOI: 10.1097/hjh.0000000000001059
|View full text |Cite
|
Sign up to set email alerts
|

Differential body weight, blood pressure and placental inflammatory responses to normal versus high-fat diet in melanocortin-4 receptor-deficient pregnant rats

Abstract: Objectives Although obesity increases the risk for hypertensive disorders of pregnancy, the mechanisms remain unclear. Neural melanocortin-4 receptor (MC4R) deficiency causes hyperphagia and obesity. Effects of MC4R deficiency on body weight, blood pressure (BP) and placental inflammatory responses to high-fat diet (HFD) are unknown. We tested two hypotheses: MC4R deficiency results in higher body weight, BP and placental inflammation under normal-fat diet (NFD) conditions and HFD exaggerates these responses i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 48 publications
1
9
0
Order By: Relevance
“…In the current study, we set forth to explore the importance of MC4R in control of blood pressure during normal pregnancy and in response to RUPP. In MC4R-def pregnant rats, we previously showed and confirmed here that they have elevated body weight, fat mass, and blood pressure under normal pregnant conditions 34 . Moreover, our novel finding is that MC4R-def pregnant rats have attenuated placental ischemia-induced hypertension.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…In the current study, we set forth to explore the importance of MC4R in control of blood pressure during normal pregnancy and in response to RUPP. In MC4R-def pregnant rats, we previously showed and confirmed here that they have elevated body weight, fat mass, and blood pressure under normal pregnant conditions 34 . Moreover, our novel finding is that MC4R-def pregnant rats have attenuated placental ischemia-induced hypertension.…”
Section: Discussionsupporting
confidence: 85%
“…Nor did this study delve into the timeframe for the development of hypertension in our obese pregnant model. We previously published that pre-pregnancy body weight is greater in MC4R-def versus that WT rats 34 . In the current study, our focus was on the impact of MC4R deficiency on placental ischemia-induced hypertension towards the end of pregnancy.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…What has been studied are the consequences of HFD on pregnancies in the P generation of dams. We previously showed that HFD feeding from early age and continued through pregnancy resulted in a slight increase in fat weight and elevated blood pressure by the end of pregnancy at gestational day 19 in rats [ 5 ]. Others have also reported that HFD promotes increased fat weight in the P generation during their pregnancies [ 6 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…The SAP elevation before pregnancy in rats with HFD (Fig 1) are associated to increases in fat abdominal volume and leptin, and a decrease in adiponectin [12]. Epidemiological and experimental studies showed that AP is elevated at the middle and at the end of gestation in obese subjects [30] but they did not examine whether AP was already elevated before pregnancy. This study reports novel findings showing that AP does not change significantly throughout gestation in rats with an early and prolonged exposure to a HFD.…”
Section: Discussionmentioning
confidence: 97%